The effect of cost of capital towards the corporate performance of public listed companies in Malaysia / Nurul Farihah Mohd Ghazali - Mohd Ghazali, Nurul Farihah (Faculty of Business Management, 2017)
Firm’s cost of capital is determined in the capital markets and is closely related to the degree of risk associated with new investments, existing assets, and the firm’s capital structure. It is an overall return that a corporation must earn on its accessible assets and business operations in order to augment or preserve the value of its current stock. The cost of capital concept is also based on the assumption that the goal of the company is to maximize shareholder wealth (Abbasi, 2003).As the result, if the company cannot meet cost of capital or expected rate of investors, the stock value of company will decline (Panahiyan &Arobzadeh. 2008). Thusa careful approximation of a firm’s specific financing and weighted-average cost of capital(WACC) is essential for a good financial management. Thus study highlights the effect of cost of capital towards company performance for a sample of 30 public listed companies in main market Bursa Malaysia for 10 years basis from 2006 to 2015. The dependent variable of this study is Return on Asset (ROA) while the independent variables are Weighted Cost of Capital (WACC), cost of debt, cost of equity, price to earnings ratio (P/E), Tobin Q and debt ratio